Polemic with the Empirical School in Galen’s Exhortation to the Study of Medicine - Koryuk, Ksenia (Hyperboreus, 2022)
Galen classifies his treatise “Exhortation” as a work against the empirical school (De libr. propr. 19. 38. 19). The extant part of the treatise, at first glance, does not contain a criticism of the empiricists. The mss of the list of Galen’s works yield the view that the title of the treatise was actually “On the treatise by Menodotus to Severus Exhortation to the study of medicine”, and some scholars believe that the second (now lost) part of the treatise could have contained a criticism of the teachings of the empiricist physician Menodotus and that this is the only way to explain the belonging of the treatise to the number of works against the empiricists. The other scholars doubt that polemics with Menodotus played any role in the treatise, and reject the alternative title. The character of Galen’s polemics against the empiricists thus remains obscure. A closer look at the content of the surviving part allows us to detect Galen’s argumentation against the empiricists at least partially. Almost half of the text is devoted to critical discourse on the harmful effects of professional athletics and the work of trainers. In one of his works (De simpl. med. temp. 11. 476. 14 – 477. 5) Galen literally puts sports trainers and an empiricist physician on a par. In his view, both the trainer and the empiricist physician practiced the same method of examination. Therefore, there is reason to believe that Galen could have chosen trainers to illustrate how the empirical method can be misused in professional practice.